PEMBUATAN PLASTIK BIODEGRADABLE DARI LIMBAH BONGGOL PISANG KEPOK DENGAN PLASTICIZER GLISEROL DARI MINYAK JELANTAH DAN KO - Indra Nafianto (Integrated Lab Journal, 2019)
Research on the manufacture of biodegradable plastic from kepok banana weevil with glycerol plasticers from used cooking oil and chitosan composites from the waste of snail shells (Achatina Fullica) was carried out. Bioplastics characteristic test results with variations in chitosan and glycerol variations have also been carried out. Based on the results of tensile strength test for the variation of chitosan and glycerol with the greatest tensile strength of 3,7321 MPa, bioplastics A2 with the composition of kepok 5 g banana starch; chitosan 0,2 g and glycerol 5 mL. The elongation test results for the most variation of chitosan and glycerol were 9,4243% are A1 bioplastics with the composition of kepok 5 g banana starch; chitosan 0,2 g and glycerol 2,5 mL. Increasing the composition of chitosan causes% swelling to decrease, while the greater the volume of glycerol added, the greater the swelling%. WVTR value will decrease with increasing composition of chitosan and glycerol. The increasing concentration of chitosan, the bioplastics will be more difficult to degenerate, while the higher the concentration of glycerol, the bioplastics sample will be easier and faster to be demoted. FTIR results indicate that synthesized bioplastics have a wavelength value similar to the constituent raw material 3425,58 (-OH); 2931,8 (-CH); 1635,64 (-NH).